The Effect of Chinese Medicine Compound in the Treatment of Rheumatoid Arthritis on the Level of Rheumatoid Factor and Anti-Cyclic Citrullinated Peptide Antibodies: A Systematic Review and Meta-Analysis - Tang, Xuan; Liu, Zehao; Yang, Zhihua; Xu, Shengmei; Wang, Maojie; Chen, Xiumin; Wen, Zehuai; Huang, Runyue (Frontiers in Pharmacology, 2021)
Objectives: To evaluate the current evidence whether Chinese medicine compound (CMC) can reduce the serum levels of rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP). Methods: We comprehensively searched PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure (CNKI), the Database for Chinese Technical Periodicals (VIP), and Wanfang data. We then performed a systematic review and meta-analysis of all randomized controlled trials (RCTs) assessing the CMC therapy methods. This study is registered with PROSPERO, number CRD42020216284. Results: In total, 65 studies were eligible for inclusion, including 6099 patients. The result of the meta-analysis showed that compared with common Western medicine therapy, CMC monotherapy or combined with Western medicine was able to reduce serum RF (SMD= -0.85, 95%CI -1.04 to -0.67) and anti-CCP (SMD= -0.56, 95%CI -0.79 to -0.32) levels to some extent. In the efficacy meta-analysis, a greater number of CMC-treated patients achieved the efficacy criteria after a period of treatment, where the relative risk (RR) was 1.20 [1.08, 1.33] for achieving ACR20, 1.57 [1.38, 1.78] for ACR50, and 2.21 [1.72, 2.84] for ACR70. At the same time, there was a statistically significant difference in the effective rate of the patient's TCM syndromes (RR=1.22, 95%CI 1.19 to 1.26). Conclusions: Through this meta-analysis and systematic review, we found that CMC for the treatment of RA is effective in reducing RF or anti-CCP levels and might have better clinical efficacy than Western medicine monotherapy. Some active components are responsible for this efficacy and worth further exploring.